1986
DOI: 10.1042/bj2340295
|View full text |Cite
|
Sign up to set email alerts
|

Role of branched-chain 2-oxo acid dehydrogenase and pyruvate dehydrogenase in 2-oxobutyrate metabolism

Abstract: Purified branched-chain 2-oxo acid dehydrogenase (BCODH) and pyruvate dehydrogenase (PDH) had apparent Km values (microM) for 2-oxobutyrate of 26 and 114, with a relative Vmax. (% of Vmax. for 3-methyl-2-oxobutyrate and pyruvate) of 38 and 45% respectively. The phosphorylation state of both complexes in extracts of mitochondria from rat liver, kidney, heart and skeletal muscle was shown to influence oxidative decarboxylation of 2-oxobutyrate. Inhibitory antibodies to BCODH and an inhibitor of PDH (3-fluoropyru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 42 publications
1
41
0
Order By: Relevance
“…Decreased levels of 2-oxobutyrate in combination with an increase in 2-aminobutyrate might favor the hypothesis of increased amino acid catabolism of threonine (Paxton et al 1986; Steele 1982). On the other hand, lower urinary excretion might also reflect an increased uptake of amino acids by the tumor for protein biosynthesis, accompanied by cellular turnover and tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased levels of 2-oxobutyrate in combination with an increase in 2-aminobutyrate might favor the hypothesis of increased amino acid catabolism of threonine (Paxton et al 1986; Steele 1982). On the other hand, lower urinary excretion might also reflect an increased uptake of amino acids by the tumor for protein biosynthesis, accompanied by cellular turnover and tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the branched-chain ␣-keto acid dehydrogenase complex (BCKDC, the rate-limiting enzyme in the BCAA catabolic pathway) affects methionine catabolism in the liver (13,14) and that leucine administration activates hepatic BCKDC in rats (15). Notwithstanding the fact that the activity level of hepatic BCKDC is markedly lower in humans than in rats (16,17), BCAA intake-induced upregulation in the liver BCKDC may be involved in the mechanism responsible for the decrease in plasma methionine concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of keto acid (2-oxobutyrate) accumulated in the culture medium was lower than the observed decrease in L-threonine levels. This may be explained by the cellular oxidation of 2-oxobutyrate through either the mitochondrial branched-chain oxoacid dehydrogenase complex or pyruvate dehydrogenase (31).…”
Section: Discussionmentioning
confidence: 99%